Effect of Vapor-Liquid Equilibrium Data on the Design of Separation Sequences by Distillation - Parodi, C. A. (2009)
An evaluation of the effect of vapor-liquid equilibrium experimental data on the design of separation sequences by distillation was done using computer simulation. Separation of a mixture of ace-tone-chloroform-benzene was chosen as an example problem. Two sequences were compared. To quantify the thermodynamic data uncertainties for each se-quence two sets of binary vapor-liquid equilibrium data were chosen. These two sets of data were used to generate simulation cases as in classical two-level fac-torial design of experiments. A third set of binary va-por-liquid experimental data allows comparing phase liquid models. For the two-column sequence, analysis done to each column alone or to the whole sequence gave the same results. In the three-column sequence, results were different and simulation of the whole se-quence gave a complete different account that simula-tion of each column alone.